Contribution of small and medium enterprises to economic development and quality of life in Turkey - Erdin, Ceren; Ozkaya, Gokhan (ELSEVIER SCI LTD, 2020)
All successful cities are the most developed and productive cities in their regions and countries in terms of economy and quality of life. In addition, it is observed that there are strong industries and enterprises in these regions and cities. Therefore, this study tries to evaluate the quality of life and the development of the industry together. The proposed method can be considered as a combination of operational research and GIS (Geographical Information System). The results of both approaches support each other. In addition, the innovative approaches of the sectors are evaluated by TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). Also, the article recommends SMEs (Small and Medium-Sized Enterprises) for sustainable economic growth. According to the results, the quality of life and socio-economic development has a very close relationship with the existence of investments and manufacturing companies. If the current development policy continues, the regions with low quality of life will continue to lag behind the other cities in terms of development. The study indicates that there are remarkable differences between eastern and western Turkey in terms of living standards and the contribution of SMEs to economic development.
Keywords: Quality of life (QOL); Sustainable development; Regional development; Small and 25 medium-sized enterprises; Geographical information system; TOPSIS; Inequality; Public economics; Economic development; Economic growth; Employment; Entrepreneurship; Business policy; Public administration; Globalization; Industrialization; Business; Economics; GIS; SYSTEMS; Science & Technology - Other Topics